Formation of new credit products in the conditions of development of socially oriented approach - Yu. V. Saakova (Путеводитель предпринимателя)
In the article questions and problems on transition of banks to more modern and effective ways of relationship and interaction with clients in the course of sales of banking products are considered. It is a consecutive orientation to the social needs of clients based on development and realization of individual banking products for clients.